Macrophage Polarization in Metabolism and Metabolic Disease - Anna Meiliana; Andi Wijaya (The Prodia Education and Research Institute (PERI), 2013)
BACKGROUND: Obesity is now recognized as the main cause of the worldwide epidemic of type 2 diabetes. Obesity-associated chronic inflammation is a contributing key factor for type 2 diabetes and cardiovascular disease. Numbers of studies have clearly demonstrated that the immune system and metabolism are highly integrated.CONTENT: Macrophages are an essential component of innate immunity and play a central role in inflammation and host defense. Moreover, these cells have homeostatic functions beyond defense, including tissue remodeling in ontogenesis and orchestration of metabolic functions. Diversity and plasticity are hallmarks of cells of the monocyte-macrophage lineage. In response to interferons (IFNs), toll-like receptor (TLR), or interleukin (IL)-4/IL-13 signals, macrophages undergo M1 (classical) or M2 (alternative) activation. Progress has now been made in defining the signaling pathways, transcriptional networks, and epigenetic mechanisms underlying M1, M2 or M2-like polarized activation.SUMMARY: In response to various signals, macrophages may undergo classical M1 activation (stimulated by TLR ligands and IFN-γ) or alternative M2 activation (stimulated by IL-4/IL-13); these states mirror the T helper (Th)1–Th2 polarization of T cells. Pathology is frequently associated with dynamic changes in macrophage activation, with classically activated M1 cells implicate in initiating and sustaining inflammation, meanwhile M2 or M2-like activated cells associated with resolution or smoldering chronic inflammation. Identification of the mechanisms and molecules that are associated with macrophage plasticity and polarized activation provides a basis for macrophage centered diagnostic and therapeutic strategies.KEYWORDS: obesity, adipose tissue, inflammation, macrophage polarization